A Cultural Content Analysis of English Textbooks Written by Native and Non-native Speakers - Ichsan Fauzi Pangestu; Henny Soepriyanti; Arafiq Arafiq; Untung Waluyo (Simpati, 2023)
The examination of cultural content in textbooks enables educators to identify suitable course materials that effectively cater to the linguistic requirements of learners in a culturally appropriate manner. This study aimed to examine the cultural aspects of the target language in high school English textbooks, specifically "Bahasa Inggris 2017 revised edition Kelas X" and "English in Mind Second Edition (Student's Book 3) for Grade X." The research used Cortazzi and Jin's checklist of cultural types and Byram's criteria of Cultural Knowledge, Cultural Awareness, and Intercultural Competence. The data was gathered from two English textbooks for tenth-grade students written by native and non-native English speakers. The findings showed that Textbook 2, English in Mind for Grade X, had a higher cultural content compared to Textbook 1, Bahasa Inggris Kelas X. Textbook 2 presented more target culture-related content, covering 188 items, International culture 64 items, and the least presented type, Source culture 28 items. Both textbooks met the cultural aspects criteria as suggested by Byram's criteria but Textbook 2 contained more target culture-related content than Textbook 1. In conclusion, the ideal textbook for presenting more target cultural content is represented by Textbook 2, which is written by native speakers of English.